Nivel de conocimiento sobre la COVID-19 en los estudiantes de medicina de la Universidad Nacional de Trujillo - Obeso Rodríguez, Kattia Analí (2021)
COVID-19 represents a threat to global health, so medical students must seek information from scientific sources to transmit valid knowledge and educate the population. Objective: To determine the level of knowledge about COVID-19 in UNT medical students Methods: Cross-sectional descriptive observational study where a validated 15-item questionnaire was carried out. Results: 88.6% of 245 students from the first to the sixth year who answered the survey expressed a high level of knowledge, 11% medium and 0.4% low. The average age was 21 to 25 years of these, 87.3% had a high level and 12.7% had a medium level. Of the female sex, 89.0% had a high level; while of the masculine 88.3%. Of the students who wanted to keep informed, 88.7% had a high level, 10.8% medium and 0.5% low. The sources most reviewed by 92.1% of students with high knowledge were websites and scientific articles, while the student with a low level used social networks and the Internet. Conclusion: UNT medical students have a high level of knowledge about COVID-19